2018
DOI: 10.1177/0890117118810247
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Parental Ethnotheories and Practices About Healthy Eating: Exploring the Developmental Niche of Preschoolers

Abstract: To understand parental ethnotheories (i.e., belief systems) and practices about preschoolers' healthy eating guided by the developmental niche framework. Design: Qualitative hermeneutic phenomenology. Setting: Home. Participants: Participants were 20 parents of preschool-age children ages 3 to 5 years, recruited from a quantitative investigation. A majority of the participants were white, female, married, well educated, and working full time. Methods: Participants who completed the quantitative survey were ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…This review includes data from 16,321 subjects reported across 20 studies. Of these, 16,064 were classified as parents with 11 studies reporting whether these were mothers ( n = 1,242) or fathers ( n = 21) 39–43,45–47,49,50 . Mean ages of parents were reported in seven studies and ranged from 30 to 35 39–41,46,47,49,52 .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review includes data from 16,321 subjects reported across 20 studies. Of these, 16,064 were classified as parents with 11 studies reporting whether these were mothers ( n = 1,242) or fathers ( n = 21) 39–43,45–47,49,50 . Mean ages of parents were reported in seven studies and ranged from 30 to 35 39–41,46,47,49,52 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twelve studies reported the educational level of parents or grandparents. Overall, grandparents tended to have less years in education than parents whereby between 17% and 100% of parents were reported to have attended higher education 39–43,45–47,49,50,54,56 whereas between 8% and 39% of grandparents had 39–41,43,54,56 …”
Section: Study Characteristicsmentioning
confidence: 99%
“…The birth of children may be the critical life event that provides an opportunity to improve parents' food literacy, particularly in light of concerns about intergenerational deskilling and/or devaluating of food skills, such as cooking [20]. Involving young children in food-related activities, such as cooking, models and contributes to their eating competence [21,22]. Little is known about how food literacy behaviors relate to parent feeding practices in Australia; however, time scarcity and responsibility divisions are likely to influence how parents operationalize practices [23].…”
Section: Introductionmentioning
confidence: 99%
“…These three systems of the developmental niche are, in turn, influenced by broader macro-level factors such as poverty, employment, and food insecurity. This theory has guided research into a number of child-related topics, including eating practices among preschoolers in the U.S. and behavioral problems among children in Nepal [36,37]. The developmental niche also provides a useful framework for examining the environmental factors shaping ECD during the first 2 years of life.…”
Section: Introductionmentioning
confidence: 99%